Zbigniew Kabata—17 March 1924–4 July 2014—Metamorphosis of a Parasitologist - Benz, George W.; Goater, Timothy M. (Zootaxa, 2016)
Birth deposits most future scientists within a standard deviation or so of average, with life proceeding with its typical bumps and ruts. For a few, however, life begins as or soon transpires into a Homeric challenge. Those who emerge from such beginnings to widely contribute to humanity become mankind’s cherished dignitaries... exemplars promulgating the legitimacy of hope and lending encouragement for progress. Zbigniew Kabata, an outstanding parasitologist and copepodologist who died at age 90 on the 4th of July 2014 in Nanaimo, British Columbia, Canada was such a giant.